2005
DOI: 10.1111/j.1742-1241.2005.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and time-course of sleep disordered breathing in patients with acute coronary syndromes

Abstract: To our knowledge, no study has examined the persistence of sleep disordered breathing in acute coronary syndrome (ACS) patients. We examined the time course of SDB in ACS patients by assessing them within days of the acute event and again after 6 months. Consecutive patients with ACS were asked to voluntarily participate in the study. Patients underwent an overnight polysomnography (PSG) approximately 3 days after the acute event. Patients with an apnea hypopnea index (AHI) > 10/h then underwent another PSG af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
0
39
1
Order By: Relevance
“…19,20,25 The present study was performed to investigate the time course of OSAHS in a homogeneous group of patients with ACS and preserved left ventricular function, who were not mechanically ventilated or on oral or intravenous sedation. To try to explain the association between ACS and OSAHS, patient selection was strict enough to exclude other comorbidities (details in the materials and methods section) that may be causative related to OSAHS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19,20,25 The present study was performed to investigate the time course of OSAHS in a homogeneous group of patients with ACS and preserved left ventricular function, who were not mechanically ventilated or on oral or intravenous sedation. To try to explain the association between ACS and OSAHS, patient selection was strict enough to exclude other comorbidities (details in the materials and methods section) that may be causative related to OSAHS.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings seem to contradict those previously reported by Bahammam et al, who showed a high prevalence of OSAHS persisting at 6 months after the acute cardiac event. 20 The question of the ideal timing of an investigation for OSAHS after an acute cardiovascular event remains unresolved. It is well known that making the diagnosis of OSAHS in patients with cardiovascular disease is important, particularly given that adequate management improves its cardiovascular consequences.…”
Section: Polysomnographymentioning
confidence: 99%
See 2 more Smart Citations
“…In Saudi Arabia, three of ten Saudi middle-aged men and four of ten Saudi middle-aged women are at a high risk of OSA 45. Additionally, 56% of Saudi patients admitted to the coronary care unit with acute coronary syndrome were diagnosed as having OSA with an apnea hypopnea index >10/hour 6. The pandemic of obesity has increased the risk of OSA, and the prevalence of obesity is expected to increase.…”
mentioning
confidence: 99%